Fluoride increases mandibular bone volume and the number of osteoblasts during pre-eruptive stage - Interlandi, Victoria (2016)
Fil: Interlandi, Victoria. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra Química Biológica A; Argentina.